DEVELOPMENT OF AN E-MODULE TO IMPROVE LEARNING OUTCOMES ON THE TOPIC OF MILLING MACHINE PARTS FUNCTIONS: PENGEMBANGAN E-MODUL UNTUK MENINGKATKAN CAPAIAN PEMBELAJARAN PADA MATERI FUNGSI BAGIAN - BAGIAN MESIN FRAIS - Firman Maulana Rusdi; Muhammad Khumaedi (SOSIOEDUKASI, 2025)
This study develops an e-module to address low student learning outcomes in the subject Milling Machine Parts Functions in vocational education. Observations showed that 36.1% of class XI TPM 1 and 37.0% of class XI TPM 2 scored in the low range (56–65), indicating difficulty understanding this core material. The issue stems from conventional lecture-based teaching and static textbooks that limit engagement and conceptual grasp. Using the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved expert validation through CVR/CVI and a quasi-experimental Pretest-Posttest Control Group Design. A Mann Whitney-Test confirmed that the e-module significantly improved learning outcomes, with the Normalized N-gain (N-gain) reaching the High effectiveness category. By integrating 3D visuals and animations, the e-module created an engaging, contextual learning experience that enhanced students technical understanding and readiness for industrial demands.